Label efficient learning of 3D point cloud recognition - Xiao, Aoran (Nanyang Technological University, 2023)
The ability to recognize the three-dimensional (3D) world profoundly impacts our comprehension, visualization, interaction, and re-creation of the physical environment. Point cloud data, renowned for its accurate representation of 3D geometric structures, has gained significant attention in both academia and industry. Meanwhile, deep neural networks (DNNs) have revolutionized various domains, including computer vision and natural language processing. Integrating point clouds with DNNs has given rise to powerful deep point cloud models, enabling enhanced recognition and understanding of the 3D world.